Framework para prospecção de dados espaciais baseado em semântica apoiado por ontologias - Guimarães, Diogo Lemos [UNESP] (2015)
With the popularity of devices it became possible to easily obtain spatial data, such as geographic points, speed and direction, and because of that it also increased considerably the interest in obtaining, storing and analyzing such data. Therefore, a larger number of applications demonstrate interest in this type of data requiring it's own databases for storing this kind of information. These bases are known as spatial databases. In order to obtain relevant information from these data, spatial data algorithms were developed and has been advancing in order to, for example, improve the quality of the results. However, current algorithms disregard that geographical points are in certain regions, which in itself, provide relevant semantic information. In order to improve the results of algorithms, the use of ontologies allows to express semantics and knowledge about a particular domain. This work presents an approach that allows, through the use of ontology, extend spatial algorithms to use a new attribute in the process of creating groups, the semantic coefficient point. Through the developed framework it is possible to adapted algorithms to use this approach enabling generate more relevant results